Depositional systems in multiphase rifts: seismic case study from the Lofoten margin, Norway. (15th February 2016) - Henstra, Gijs A.; Gawthorpe, Robert L.; Helland‐Hansen, William; Ravnås, Rodmar; Rotevatn, Atle
Abstract: The evolution of depositional systems in multiphase rifts is influenced by the selective reactivation of faults between subsequent rift phases. The Middle Jurassic to Palaeocene tectonic history of the Lofoten margin, a segment of the North Atlantic rift system, is characterised by three distinct rift phases separated by long (>20 Myr) inter‐rift periods. The initial rift phase comprised a distinct fault initiation and linkage stage, whereas the later rift phases were characterised by selective reactivation of previously linked through‐going faults which resulted in immediate rift climax. Using 2‐D and 3‐D seismic reflection data in conjunction with shallow core data we present a 100 Myr record of shallow to deep marine depositional environments that includes deltaic clinoform packages, slope aprons and turbidite fans. The rapid re‐establishment of major faults during the later rift phases impacts on drainage systems and sediment supply. Firstly, the immediate localisation of strain and accumulation of displacement on few faults results in pronounced footwall uplift and possible fault block rotation along those faults, which makes it more likely for any antecedent fault‐transverse depositional systems to become reversed. Secondly, any antecedent axially‐sourced depositional systems that are inherited from the foregoing rift phase(s) are likely to be sustained after reactivation because such axial systems have already been directed around fault tips. Hence, the immediate localisation of strain through selective reactivation in the later rift phases restricts fault‐transverse sediment supply more than axial sediment supply, which is likely to be a key aspect of the tectono‐sedimentary evolution of multiphase rifts.